2017
DOI: 10.1007/s00213-017-4759-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased cocaine and amphetamine-regulated transcript cord blood levels in the newborns exposed to crack cocaine in utero

Abstract: The increase in CART levels in EN UBC suggests a response to crack/cocaine-induced oxidative stress during gestational period, as a potential attempt of neuroprotection. In adult women in puerperium, however, this endogenous antioxidant recruitment does not seem to operate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…A preocupação se estende para a vida do feto e dos recém-nascidos, uma vez que a cocaína e seus metabólitos ficam armazenados tanto no miométrio e membrana placentária, como são liberados no líquido amniótico, gerando uma exposição lenta do feto à cocaína. Estudos comprovam que a exposição pré-natal ao crack/cocaína está associada a déficits neurocomportamentais, que podem se manifestar no desenvolvimento da criança no início da infância até a adolescência (PARCIANELLO RR, et al, 2017).…”
Section: Discussionunclassified
“…A preocupação se estende para a vida do feto e dos recém-nascidos, uma vez que a cocaína e seus metabólitos ficam armazenados tanto no miométrio e membrana placentária, como são liberados no líquido amniótico, gerando uma exposição lenta do feto à cocaína. Estudos comprovam que a exposição pré-natal ao crack/cocaína está associada a déficits neurocomportamentais, que podem se manifestar no desenvolvimento da criança no início da infância até a adolescência (PARCIANELLO RR, et al, 2017).…”
Section: Discussionunclassified
“…Drug use during pregnancy can bring consequences to babies. Recent studies show babies with smaller than normal head circumference, lower birth weight, premature birth, congenital malformations, and future problems such as neurobehavioral problems in childhood and adolescence [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…The Childhood and Youth Report 12 stated that approximately 29 thousand children and adolescents were in institutional care in Brazil, mainly due to parents/guardians being chemical/alcohol dependent (81%) and negligent (81%). Several studies have shown results of alterations in children whose mothers have used drugs during pregnancy [6][7][8][9][10][11][12] , because the drug metabolism is delayed due to the decreased expression of plasma and liver cholinesterases 13 , alterations such as: placental abruption, congenital malformation, premature birth, low birth weight, smaller head circumference, among other alterations [14][15][16] . In older children and teenagers, the most commonly found problems are behavioral and cognitive 17 .…”
Section: Introductionmentioning
confidence: 99%